Thursday

April 24, 2014

April 24, 2014

Posted by **Chelsea** on Friday, October 22, 2010 at 8:13pm.

y = (cx)/(1 + cx)

g(x) = 1 + cx

f(x) = cx

Using the quotient rule:

y' = [(1 + cx)(f') - (cx)(g')]/(1 + cx)^2

How do you find f' and g' when there is more than one variable? Having a C and an X?

- Calc -
**jai**, Saturday, October 23, 2010 at 4:25amwas it also said that you would treat c as another variable? because in most problems, c is treated as a constant.

thus:

f'(x) = c

g'(x) = c

**Related Questions**

calc II - Express the integrals as the sum of partial fractions and evaluate the...

math - how can i find c , f', g' from (1+cx)(f')-cx(g')/(1+cx)^2

English - Write CX before each complex sentence. Write CP before each compound ...

MATH - Suppose that g(X)=f(cx). Show from the definition that g'(x)=cf'(cx)

Calculus - OK trying again. For what (numerical) of the constant "c" is the ...

calculus - Find the value of the constant C that makes the following function ...

Calculus - For some reason the answer to this question is alluding me, Im sure ...

Partial Fractions - I think- and this is just out loud- that you would do (Cx + ...

Calculus - F(x) = 1-x and g(x) = 1/x Write in the form (ax + b)/(cx + d) a.What ...

for Knights - have been looking at your post ... http://www.jiskha.com/display....